Computer Activity and Features of Play in Preschoolers - Salomatova O.V (Moscow State University of Psychology and Education, 2022)
The article presents the results of an empirical study focusing the uniqueness of the play activity of contemporary Russian preschoolers, as well as on identifying the relationship of the features of play activity with the child's screen time. Research methods applied include "Method of diagnostics of role-playing games" by E.O. Smirnova and I.A. Ryabkova and "Diagnostics of the development of playing skills" by R.R. Kalinina, as well as a questionnaire, elaborated by the author to evaluate different aspects of children's interaction with digital content. The empirical study was conducted from December 2019 to January 2021. 13 children between 4 and 6 years of age participated in the longitudinal study. The analysis of the collected data showed that screen time influences such characteristics of play as subject substitution; interaction, organizing the play; plot elaboration; role behavior; play actions; the use of attributes and implementation of rules. These characteristics have an inverse relationship with the child's screen time.